Assessing the impact of transfusion thresholds in patients with septic acute kidney injury: a retrospective study - Ruan, Xiangyuan; Wang, Baoxin; Gao, Yifan; Wu, Jinmei; Yu, Xueshu; Liang, Chenglong; Pan, Jingye (Frontiers in Medicine, 2023)
Background Sepsis is a severe condition that often leads to complications such as acute kidney injury, which significantly increases morbidity and mortality rates. Septic AKI (S-AKI) is common in ICU patients and is associated with poor outcomes. However, there is no consensus on the optimal transfusion threshold for achieving the best clinical results. This retrospective study aims to investigate the relationship between different transfusion thresholds during hospitalization and the prognosis of septic AKI. Methods Data from patients with S-AKI was extracted from MIMIC-IV. Based on the lowest hemoglobin level 24 h before transfusion, patients were divided into high-threshold (≥7 g/L) and low-threshold (<7 g/L) groups. We compared the outcomes between these two groups, including hospital and ICU mortality rates as primary outcomes, and 30 days, 60 days, and 90 days mortality rates, as well as duration of stay in ICU and hospital as secondary outcomes. Results A total of 5,654 patients were included in our study. Baseline characteristics differed significantly between the two groups, with patients in the low-threshold group generally being younger and having higher SOFA scores. After performing propensity score matching, no significant differences in survival rates were found between the groups. However, patients in the low-threshold group had a longer overall hospital stay. Conclusion A lower transfusion threshold does not impact the mortality rate in S-AKI patients, but it may lead to a longer hospital stay.